Sorogan as Islamic Personalized Pedagogy: Its Effect on Nahwu Learning Outcomes at Pondok Pesantren KH. Syamsuddin Durisawo Ponorogo: (Sorogan sebagai Pedagogi Personalisasi Islam: Pengaruhnya terhadap Hasil Belajar Nahwu di Pondok Pesantren KH. Syamsuddin Durisawo Ponorogo) - Muhammad Ainur Rohman; Retno Widyaningrum (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2026)
Purpose: This study examines the effect of Personalized Sorogan-Based Learning (PPS) on santri Nahwu learning outcomes at Pondok Pesantren KH. Syamsuddin Durisawo Ponorogo. Method: The study employed a quantitative correlational design with an ex post facto orientation. PPS was measured using a 25-item Likert-scale questionnaire covering learning pace adjustment, material adjustment, repetition, individual handling of grammatical errors, and direct ustaz guidance. Nahwu learning outcomes were measured through documented Nahwu learning outcome scores. The sample consisted of 53 santri selected from an accessible population of 110 through Slovin's formula and proportionate stratified random sampling. The data were analyzed using validity and reliability tests, descriptive statistics, residual normality and linearity tests, Pearson correlation, and simple linear regression. Findings: The PPS questionnaire showed excellent internal consistency with Cronbach's Alpha = 0.990. Simple linear regression indicated that PPS had a significant positive effect on Nahwu learning outcomes, B = 0.642, t = 14.368, p < 0.001. The model produced R Square = 0.802, meaning that PPS statistically explained 80.2% of the variance in documented Nahwu learning outcome scores within the sample. Future Research: Future studies may examine feedback intensity, learning motivation, prior Arabic competence, frequency of sorogan sessions, teacher-student ratio, and longitudinal achievement data to clarify the learning mechanisms behind sorogan-based instruction. Implications: The findings provide a quantitative basis for strengthening sorogan as an individualized pesantren pedagogy through paced progression, repeated practice, individual correction, and direct grammatical guidance. Novelty: The novelty of this study lies in reframing sorogan as a measurable form of personalized learning and testing its statistical effect on Nahwu achievement in a pesantren-based Arabic grammar learning context.